2012
DOI: 10.1093/hmg/dds381
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of genome-wide association studies of breast cancer identifies two novel susceptibility loci at 6q14 and 20q11

Abstract: Genome-wide association studies (GWAS) of breast cancer defined by hormone receptor status have revealed loci contributing to susceptibility of estrogen receptor (ER)-negative subtypes. To identify additional genetic variants for ER-negative breast cancer, we conducted the largest meta-analysis of ER-negative disease to date, comprising 4754 ER-negative cases and 31 663 controls from three GWAS: NCI Breast and Prostate Cancer Cohort Consortium (BPC3) (2188 ER-negative cases; 25 519 controls of European ancestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 28 publications
5
144
1
1
Order By: Relevance
“…Genotypes at many millions of common variants across the genome can be genotyped or imputed with high accuracy using largescale genotyping arrays, using reference panels from the 1000 Genomes Project (Auton et al 2015). This approach has been applied with great success in cancer epidemiology in the general population, with GWAS having identified more than 100 common susceptibility variants for breast cancer , Hunter et al 2007, Stacey et al 2007, Ahmed et al 2009, Thomas et al 2009, Antoniou et al 2010b, Turnbull et al 2010, Cai et al 2011, Fletcher et al 2011, Ghoussaini et al 2012, Hein et al 2012, Long et al 2012, Siddiq et al 2012, Bojesen et al 2013, French et al 2013, Garcia-Closas et al 2013, Gaudet et al 2013, Meyer et al 2013, Cai et al 2014, Milne et al 2014a, Orr et al 2015, Couch et al 2016, Dunning et al 2016, Lawrenson et al 2016, Zheng et al 2009) and 22 for ovarian cancer (Song et al 2009, Bolton et al 2010, Goode et al 2010, Bojesen et al 2013, Permuth-Wey et al 2013, Pharoah et al 2013, Kuchenbaecker et al 2015.…”
Section: Genetic Modifiersmentioning
confidence: 99%
“…Genotypes at many millions of common variants across the genome can be genotyped or imputed with high accuracy using largescale genotyping arrays, using reference panels from the 1000 Genomes Project (Auton et al 2015). This approach has been applied with great success in cancer epidemiology in the general population, with GWAS having identified more than 100 common susceptibility variants for breast cancer , Hunter et al 2007, Stacey et al 2007, Ahmed et al 2009, Thomas et al 2009, Antoniou et al 2010b, Turnbull et al 2010, Cai et al 2011, Fletcher et al 2011, Ghoussaini et al 2012, Hein et al 2012, Long et al 2012, Siddiq et al 2012, Bojesen et al 2013, French et al 2013, Garcia-Closas et al 2013, Gaudet et al 2013, Meyer et al 2013, Cai et al 2014, Milne et al 2014a, Orr et al 2015, Couch et al 2016, Dunning et al 2016, Lawrenson et al 2016, Zheng et al 2009) and 22 for ovarian cancer (Song et al 2009, Bolton et al 2010, Goode et al 2010, Bojesen et al 2013, Permuth-Wey et al 2013, Pharoah et al 2013, Kuchenbaecker et al 2015.…”
Section: Genetic Modifiersmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) and candidate gene studies have identified more than 75 SNPs that may be associated with risk of breast cancer in Caucasians (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). It has been estimated that there is about a 10% overlap in the genetic factors that influence breast cancer risk and those that determine variation in MD (5).…”
Section: Introductionmentioning
confidence: 99%
“…have also been identified [19] to be associated with breast cancer. In addition, more than 40 novel breast cancer susceptibility loci have been found in a most recent meta-analysis of nine GWAS studies [20,21]. As breast cancer involves multiple cancer susceptibility alleles, the patient's mother might carry another breast cancer gene mutation that had not yet be identified.…”
Section: Discussionmentioning
confidence: 99%